Optimization of droplet digital PCR assays for the type-specific detection and quantification of five HPV genotypes, including additional data on viral loads of nine different HPV genotypes in cervical carcinomas - Malin, Kaliff; Louise, Bohr Mordhorst; Gisela, Helenius; Mats, Karlsson G.; Gabriella, Lillsunde-Larsson (Journal of virological methods, 2021)
•Droplet digital PCR (ddPCR) assays for HPV genotype-specific quantification of five HPV genotypes were optimized.•The method for HPV viral load analysis showed to be suitable both in formalin-fixed paraffin-imbedded and cytology tissue.•Total HPV viral load in multiple- and single-HPV genotype infected cervical tumor samples were analyzed.•Women’s age of 60 years or older and certain HPV genotypes and genotype genera were associated with higher VL. The droplet digital PCR (ddPCR) system enables high-sensitivity detection of nucleic acids and direct absolute quantification of the targets. The aim of this research was to evaluate this system for viral load (VL) analysis of the human papillomavirus (HPV) genotypes HPV31, 35, 39, 51 and 56 measured in number of viral particles per cell. The sample types used for the optimization of the ddPCR assay were formalin-fixed paraffin-embedded (FFPE) tissues and cervical liquid cytology samples. The presently optimized ddPCR assays, together with assays optimized previously for HPV16, 18, 33 and 45, with the same ddPCR method, were used for the VL analysis of cervical tumor samples. Results published previously on the present study cohort showed that women with a cervical tumor containing multiple high-risk HPV genotypes had a worse prognosis compared to women with single-genotype-infected tumors. The VL was therefore analyzed in this study for the same cohort, as a possible explanatory factor to the prognostic differences. The results of the optimization part of the study, with analysis of VL using ddPCR in DNA from varying sample types (FFPE and liquid cytology samples), showed that each of the five assays demonstrated good inter- and intra-assay means with a coefficient of variation (CV) under 8% and 6% respectably. The cohort results showed no difference in VL between tumors with multiple and single HPV infections, and therefore did most likely not constitute a contributing factor for prognostic differences observed previously. However, tumors from women aged 60 years or older or containing certain HPV genotypes and genotype genera were associated with a higher VL.